Systematic Literature Review: Optimizing Broiler Chicken Cage Temperature and Humidity - Fidel Lusiana Putri; Deva Kurnia Setiawan; Arsmanda Adi Nugraha; Feddy Setio Pribadi; Rizky Ajie Aprilianto (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
Broiler production is highly dependent on environmental conditions, especially temperature and humidity in the cage. This research is a Systematic Literature Review that uses the PRISMA method to optimize the temperature and humidity of broiler cages. A total of 202 journals were found through Google Scholar and other repositories, with an additional 16 journals manually. After filtering, 38 journals were selected based on publication year 2019-2024. From the review of the selected literature, five research questions were derived that led to new understanding and solutions to the problems in the research topic. The results show that temperature and humidity significantly impact broiler performance, including health, welfare, and productivity. An IoT-based monitoring and control system is proven to assist with real-time monitoring and control of temperature and humidity, improving farm efficiency and effectiveness. Supporting factors for implementing this system include a friendly user interface, mobile applications, and real-time notifications. The application of IoT technology in broiler farming has the potential to provide significant benefits to farmers and the livestock industry as a whole.